Effect of land use and hydrological processes on Escherichia coli concentrations in streams of tropical, humid headwater catchments - Rochelle-Newall, Emma J.; Ribolzi, Olivier; Viguier, Marion; Thammahacksa, Chanthamousone; Silvera, Norbert; Latsachack, Keooudone; Dinh, Rinh Pham; Naporn, Piyapong; Sy, Hai Tran; Soulileuth, Bounsamay; Hmaimum, Nikom; Sisouvanh, Pem; et al. (Scientific reports, 2016)
Lack of access to clean water and adequate sanitation continues to be a major brake on development. Here we present the results of a 12-month investigation into the dynamics of Escherichia coli , a commonly used indicator of faecal contamination in water supplies, in three small, rural catchments in Laos, Thailand and Vietnam. We show that land use and hydrology are major controlling factors of E. coli concentrations in streamwater and that the relative importance of these two factors varies between the dry and wet seasons. In all three catchments, the highest concentrations were observed during the wet season when storm events and overland flow were highest. However, smaller peaks of E. coli concentration were also observed during the dry season. These latter correspond to periods of intense farming activities and small, episodic rain events. Furthermore, vegetation type, through land use and soil surface crusting, combined with mammalian presence play an important role in determining E. coli loads in the streams. Finally, sampling during stormflow revealed the importance of having appropriate sampling protocols if information on maximum contamination levels is required as grab sampling at a fixed time step may miss important peaks in E. coli numbers.